2021
DOI: 10.1177/03000605211040976
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Kimura’s disease and angiolymphoid hyperplasia with eosinophilia: case reports and literature review

Abstract: Kimura’s disease (KD) is a rare chronic inflammatory or allergic disease. Angiolymphoid hyperplasia with eosinophilia (ALHE) is a benign vascular neoplasm. Their relationship has always been debated. This article reports two rare cases, one of each disease. One patient was a 48-year-old female that presented with a mass on her right mandible. She also had oedema erythema and wheals on her lower limbs. She was diagnosed with Kimura’s disease complicated with chronic urticaria. The second patient was a 23-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 19 publications
(42 reference statements)
0
27
0
7
Order By: Relevance
“…The usual presentation involves progressively enlarging painless nodules accompanied by increased levels of eosinophils and IgE. KD classically involves the head and neck region, with typical features of peripheral eosinophilia and raised serum IgE 1 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The usual presentation involves progressively enlarging painless nodules accompanied by increased levels of eosinophils and IgE. KD classically involves the head and neck region, with typical features of peripheral eosinophilia and raised serum IgE 1 …”
Section: Discussionmentioning
confidence: 99%
“…Our patient's clinicopathological presentation supported the diagnosis of KD. Clinical features suggestive of KD include age of onset at 20–40 years, South Asian ethnicity, mass size of 10–200 mm, and raised levels of eosinophilis and serum IgE 1 . By contrast, EH is reported more commonly in women in the third to the fifth decade of life, with associated overlying erythema, normal serum IgE and occasional eosinophilia 1 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diffusion-weighted imaging (DWI) showed hyperintensity, and a contrast-enhanced scan showed obvious homogeneous enhancement, which was considered as an enlarged lymph node, but the benign and malignant lesions could not be determined. To further systematically evaluate the patient's whole-body condition, the patient underwent 18 F-FDG PET/CT examination (as shown in Figure 2), of which results showed that there were multiple nodules with increased radioactivity uptake of different sizes in the left inguinal region, with maximum standard uptake value (SUVmax) ranging from 4.5 to 5.3, and no obvious abnormal radioactive uptake foci were found in the rest of the body. The lesion was limited and surgical resection was feasible for this patient, so he underwent left groin mass excision under local anesthesia.…”
Section: Case Descriptionmentioning
confidence: 99%